The generative function of the occlusion map: Square spirals and the structure of visibility. (March 2023) - Christenson, Mike
Abstract : Le Corbusier's projects instantiating his concept for the Museum of Unlimited Extension share a common structure of visibility, revealing and obscuring views of the horizon. A diagram of this structure, called the occlusion map, can generate floor plans consistent with the structure of visibility in the Museum of Unlimited Extension. This paper highlights capabilities of digital tools for revealing latent attributes of existing buildings. By generating a population of floor plans, we hope to show an untapped possibility of generative design strategies – beyond the possibility of generating novel architectural form, we discuss the possibility of "designerly analysis" aimed at disclosing latent architectural attributes of existing form. Highlights: An analysis of Le Corbusier's spiral museum designs leads to a generative algorithm. Shared features of visibility and occlusion are identified and generalized. A population of new floor plans is generated.